2012
DOI: 10.3389/fnint.2012.00059
|View full text |Cite
|
Sign up to set email alerts
|

EEG alpha activity reflects motor preparation rather than the mode of action selection

Abstract: Alpha-band activity (8–13 Hz) is not only suppressed by sensory stimulation and movements, but also modulated by attention, working memory and mental tasks, and could be sensitive to higher motor control functions. The aim of the present study was to examine alpha oscillatory activity during the preparation of simple left or right finger movements, contrasting the external and internal mode of action selection. Three preparation conditions were examined using a precueing paradigm with S1 as the preparatory and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
44
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 60 publications
6
44
1
1
Order By: Relevance
“…Thus, the long‐lasting ERD increase may be explained with preparation for the movement required for a response, and this preparation seems to begin immediately with the beginning of the stimulus sequence as much as 10 s before actual movement execution. Alpha ERD during movement preparation has been reported previously and was interpreted as preparing for a motor task but does not reflect processing for the specific task itself (Deiber et al, ). The alpha ERD in the sensorimotor system may support the concept of a preparatory role of alpha ERD.…”
Section: Discussionmentioning
confidence: 79%
“…Thus, the long‐lasting ERD increase may be explained with preparation for the movement required for a response, and this preparation seems to begin immediately with the beginning of the stimulus sequence as much as 10 s before actual movement execution. Alpha ERD during movement preparation has been reported previously and was interpreted as preparing for a motor task but does not reflect processing for the specific task itself (Deiber et al, ). The alpha ERD in the sensorimotor system may support the concept of a preparatory role of alpha ERD.…”
Section: Discussionmentioning
confidence: 79%
“…Interestingly, Kayser et al (2010a) found that the FRN-related source asymmetry linked to manual response versus silent count of target tones was reduced in schizophrenia. Predominant right parieto-occipital alpha ERD has also been reported for right-handed healthy adults during the anticipatory S1-S2 interval of a cued motor response task, particularly for participants with weak lateralization of sensorimotor alpha activity, suggesting distinct alpha asymmetry patterns associated with motor or attentional processes (Deiber et al, 2012). However, more research is required to clarify the mechanisms underlying these alpha ERD effects.…”
Section: Discussionmentioning
confidence: 94%
“…With respect to sensorimotor involvement, alpha ERS is thought to indicate an inhibited or deactivated motor region while ERD is thought to reflect an active brain region engaged in motor execution (Neuper, Woertz & Pfurtscheller, 2006;Deiber et al, 2012). In terms of attentional control, alpha ERS is linked to the successful inhibition of brain regions not necessary for stimulus processing or maintenance (Cooper et al, 2003;Klimesch, 2012), thereby facilitating the reduction of potentially distracting information (Sauseng et al, 2009).…”
Section: Electrophysiological Findingsmentioning
confidence: 99%